Pengaruh Penerapan Electronic Health Record (EHR) Terhadap Perkem- bangan Kognitif Perawat: Literatur Review - Yustina, Anita (Indonesian Academia Health Sciences Journal, 2020)
Objective: to identify Effect of Application of Electronic Health Record (EHR) on Nurses’ Cognitive Development . Methods: This article The article search was carried out on databases : ProQuest, and Google Scholar, using keywords System Information,. The number of articles reviewed was 10 articles Results: The implementation of electronic health records is accelerated in a worldwide clinical framework in an effort to improve patient safety and improve efficiency relat- ed to the provision of care.Social cognitive theory considering variations in thinking about electronic health nurses can influence the level of benefits realized, the purpose of this meaning is to discuss about the use of social cognitive theory to help organiza- tions that use electronic health records to facilitate adoption more in line with this type of clinical technology. Conclusion: It is recommended to further researchers to be able to use social cognitive theory as a support to adopt future technology in increasing the role of nurses in pro- viding effective and efficient services.